STUDI KEBIJAKAN LOKAL BAGI WARIA SEBAGAI WARGA NEGARA DALAM UPAYA PENCEGAHAN HIV/AIDS DI PROVINSI DIY TAHUN 2012 - , SISILYA OKTAVIANA BOLILANGA, Dr. Anna Marie Wattie, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objectives of this study is to examine the implementation of local policies in education, health, social and employment as prevention of HIV/AIDS based on organizational capacity and perceptions of beneficieries in DIY Province. The aspiration from beneficieries offering policy recommendation to formulate the new policy or reformulation existing local policies for waria. A qualitative approach through in-depth interviews, FGD, observation and study documentation used to obtain descriptions policy implementation. Implementation of existing local policies awareness of the organization's policies describe transvestites, although confined to the areas of health, social and employment. Best practices obtained